CCAT1 promotes laryngeal squamous cell carcinoma cell proliferation and invasion - Zhuang, Kun (Am J Transl Res, 2016)
Long noncoding RNAs (lncRNAs) are proved tobe deregulated in a number of cancers and play important roles in tumor biology. Colon cancer-associated transcript-1 (CCAT1) was initially found in colon cancer and promoted cancer cell development. However, the role of CCAT1 in laryngeal squamous cell carcinoma (LSCC) is still unknown. In this study, we demonstrated that CCAT1 expression was upregulated in the LSCC tissues compared with the normal adjacent tissues. Moreover, CCAT1 expression was higher in LSCC tissues thanin adjacent normal tissues in 70% of patients. In addition, higher expression of CCAT1 was correlated with T3-4 grade and advanced clinical stage. Overexpression of CCAT1 promoted Hep-2 cell proliferation, migration and invasion. Ectopic expression of CCAT1 suppressed E-cadherin expression while enhanced the expressionof N-cadherin and Vimentin. Furthermore, CCAT1 overexpression increased Hep-2 cell colony formation and cell cycle. We also demonstrated that CCAT1 overexpression suppressed the expression of let-7 and enhanced the expression of HMGA2 and Myc, the direct target genes of let-7. To conclude, our data demonstrated that CCAT1 played an oncogenic role in the development of LSCC.